2018
DOI: 10.1021/acsomega.7b01212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dimethyl Sulfoxide on the Binding of 1-Adamantane Carboxylic Acid to β- and γ-Cyclodextrins

Abstract: Most therapeutic targets are proteins whose binding sites are hydrophobic cavities. For this reason, the majority of drugs under development are hydrophobic molecules exhibiting low solubility in water. To tackle this issue, a few percent of cosolvent, such as dimethyl sulfoxide (DMSO), is usually employed to increase drug solubility during the drug screening process. However, the few published studies dealing with the effect of adding DMSO showed that the affinity of hydrophobic ligands is systematically unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…While the guest‐water interactions can effectively be assessed by comparing experimental and calculated free energies of hydration, a quantity often used as target in force field optimization , , the host‐water and host‐guest interactions usually rely on parameter transferability arguments and combining rules for cross‐terms. To further localize the most appropriate degrees of freedom for force field refinement, it might be useful to consider quantities such as the osmotic pressure or activity coefficients that may help to improve the balance between the various force field terms , but also to expand the diversity of experimentally studied systems including modifications of the host molecules as well as considering more complex solvent environments .…”
Section: Benchmark Studies On Host‐guest Systemsmentioning
confidence: 99%
“…While the guest‐water interactions can effectively be assessed by comparing experimental and calculated free energies of hydration, a quantity often used as target in force field optimization , , the host‐water and host‐guest interactions usually rely on parameter transferability arguments and combining rules for cross‐terms. To further localize the most appropriate degrees of freedom for force field refinement, it might be useful to consider quantities such as the osmotic pressure or activity coefficients that may help to improve the balance between the various force field terms , but also to expand the diversity of experimentally studied systems including modifications of the host molecules as well as considering more complex solvent environments .…”
Section: Benchmark Studies On Host‐guest Systemsmentioning
confidence: 99%
“…For RAME--CD and HP--CD derivatives ( Table 2, entries 9-12), the variation of CAC are less marked. [25] The spectrum showed also correlation spots between the internal CD protons and the protons of the aliphatic chain (see supporting information). These values indicated that they possessed a good surface activity compared to the native CDs which are not surface active.…”
Section: Resultsmentioning
confidence: 87%
“…Compared to a previously study on the binding constant of the bis(pyridinium)-xylylene moiety with CB7, 32 we obtained a relatively lower K value (1.53 ± 0.82 × 10 4 M −1 ), which was presumably due to solvent DMSO; this solvent fits better into the cavity of a hydrophobic binding site than water. 33 To re-evaluate the binding affinity of CB7 to BH1, the data obtained from UV-Vis titration experiments of BH1 versus CB7, monitored at 330, 340, 360, 366, and 378 nm, were fitted according to the 1 : 1 binding isotherm on the website (Fig. S12 † ), 34 which showed a similar binding constant (4.05 × 10 4 M −1 ).…”
Section: Resultsmentioning
confidence: 99%